Odpowiedź :
Odpowiedź:
a)
16−2x=2x+6
-2x - 2x = 6 - 16
-4x = -10 /:(-4)
x = 10/4 = 2 2/4 = 2 1/2
b)
4+3x=7x+12
3x - 7x = 12 - 4
-4x = 8 /:(-4)
x = -2
c)
15−6x=3x+7
-6x - 3x = 7 - 15
-9x = -8 /:(-9)
x = 8/9
d)
2(4x − 6) = 3(5 −3x)
8x - 12 = 15 - 9x
8x + 9x = 15 + 12
17x = 17 /:17
x = 1
e)
3(4x − 5) = 4(3 −5x)
12x - 15 = 12 - 20x
12x + 20x = 12 + 15
32x = 27 /:32
x = 27/32
f)
4(2x − 4) = 3(6 −2x)
8x - 16 = 18 - 6x
8x + 6x = 18 + 16
14x = 34 /:2
7x = 17 /:7
x = 17/7
nastepne przyklady nie sa rownaniami
nie ma w nich zmiennej
g) 3 − 14 = 5 − +3 2
h) 2−14 + 12 = 4 − 3 − 2 8
i) +12 − 2−13 = 3−14 − 3 − 2 3
Szczegółowe wyjaśnienie:
Odpowiedź:
1)
16−2x=2x+6
-2x - 2x = 6 - 16
-4x = -10 /:(-4)
x = 10/4 = 2 2/4 = 2 1/2
2)
4+3x=7x+12
3x - 7x = 12 - 4
-4x = 8 /:(-4)
x = -2
3)
15−6x=3x+7
-6x - 3x = 7 - 15
-9x = -8 /:(-9)
x = 8/9
4)
2(4x − 6) = 3(5 −3x)
8x - 12 = 15 - 9x
8x + 9x = 15 + 12
17x = 17 /:17
x = 1
5)
3(4x − 5) = 4(3 −5x)
12x - 15 = 12 - 20x
12x + 20x = 12 + 15
32x = 27 /:32
x = 27:32
6)
4(2x − 4) = 3(6 −2x)
8x - 16 = 18 - 6x
8x + 6x = 18 + 16
14x = 34 /:2
7x = 17 /:7
x = 17:7
7) 3 − 14 = 5 − +3 2
8) 2−14 + 12 = 4 − 3 − 2 8
9) +12 − 2−13 = 3−14 − 3 − 2 3